The power of market fundamentalism : Karl Polanyi's critique - Block, Fred L.; Somers, Margaret R. (Harvard University Press, 2014)
What is it about free-market ideas that give them tenacious staying power in the face of such manifest failures as persistent unemployment, widening inequality, and the severe financial crises that have stressed Western economies over the past forty years? Fred Block and Margaret Somers extend the work of the great political economist Karl Polanyi to explain why these ideas have became the dominant economic ideology of our time.